A systematic review of interventions to improve the dietary intake, physical activity and weight status of children attending family day care services. Issue 12 (8th August 2020) - Yoong, Sze Lin; Lum, Melanie; Jones, Jannah; Kerr, Erin; Falkiner, Maryann; Delaney, Tessa; McCrabb, Sam; Chai, Li Kheng; Seward, Kirsty; Grady, Alice
Abstract: Objective: To (i) identify and synthesise findings from interventions to improve the dietary intake, physical activity and weight status of children aged 0–6 years attending family day care services; and (ii) assess the impact of interventions on family day care environments, intervention cost and adverse outcomes. Design: Medline in Process, PsycINFO, ERIC, Embase, CINAHL, CENTRAL and Scopus databases were searched in March 2019. Studies were included if they (i) evaluated an intervention to improve the diet, physical activity and/or weight of children aged 0–6 years; (ii) were delivered in family day care services; (iii) targeted child diet, physical activity and/or weight; and (iv) used a parallel control group design. Screening was undertaken by two reviewers with disagreements resolved by a third reviewer. Setting: Family day care services, also known as family childcare homes. Participants: Children aged 0–6 years attending family day care services. Results: In total, 8977 titles were retrieved, and 199 full-texts reviewed. No studies met the inclusion criteria for the primary outcome; however, two studies reporting on the secondary outcome of family day care environments were included. The 4-year community-wide obesity prevention programme and the 12-month train-the-trainer programme both reported statistically significant improvements in the healthy eating and physical activity environments of family day care, compared to cross-sectional state-average control groups. Conclusions: Findings highlight few existing interventions in family day care services and a need for high-quality controlled trials to identify effective interventions to improve children's diet, activity and weight in this setting.